Optimality test in fuzzy inventory model for restricted budget and space: Move forward to a non-linear programming approach - Pattnaik, M. (Yugoslav Journal of Operations Research; Vol 25 No 3 (2015): Vol. 25 No. 3, 2016)
In this paper the concept of fuzzy Non-Linear Programming Technique is applied to solve an economic order quantity (EOQ) model for restricted budget and space. Since various types of uncertainties and imprecision are inherent in real inventory problems, they are classically modeled by using the approaches from the probability theory. However, there are uncertainties that cannot be appropriately treated by usual probabilistic models. The questions which arise are how to define inventory optimization tasks in such environment and how to interpret the optimal solutions. This paper allows the modification of the Single item EOQ model in presence of fuzzy decision making process where demand is related to the unit price and the setup cost varies with the quantity produced/Purchased. We consider the modification of objective function, budget and storage area in the presence of imprecisely estimated parameters. The model is developed for the problem by employing different modeling approaches over an infinite planning horizon. It incorporates all the concepts of a fuzzy arithmetic approach, the quantity ordered and the demand per unit compares both fuzzy non linear and other models. Investigation of the properties of an optimal solution allows developing an algorithm whose validity is illustrated through an example problem by using MATLAB (R2009a) version software